Association Between Fish Consumption and Nephropathy in American Indians—The Strong Heart Study - Lee, Cheetin Christine (2011)
OBJECTIVE: The present study examined the association between fish consumption and nephropathy in American Indians. METHODS: In the family cohort of the Strong Heart Study, we investigated 2,261 participants with baseline examination between 2001 and 2003 and follow-up examination between 2006 and 2008. The average follow-up period was 5.4 years. We defined fish consumption as the sum of dietary intake of tuna, fried fish, and nonfried fish obtained from a validated food frequency questionnaire. Nephropathy was defined as microalbuminuria (urinary albumin–creatinine ratio [ACR]: 30 to 299 mg/g), macroalbuminuria (urinary ACR: ≥300 mg/g), or an estimated glomerular filtration rate of <60 mL/min/1.73 m(2). Using regression models, we examined the association between fish consumption measured at baseline and 2 outcomes in nephropathy present at follow-up, albuminuria, or renal impairment, and change in urinary ACR or estimated glomerular filtration rate between baseline and follow-up examinations. RESULTS: The prevalence of microalbuminuria, macroalbuminuria, and renal impairment was 13%, 3%, and 4%, respectively. The fish items consumed by the participants were predominantly deep-fried. We found no associations between fish consumption and any measure of nephropathy after adjusting for demographic, clinical, lifestyle, and dietary factors. CONCLUSIONS: Dietary intake of predominantly fried fish was not associated with a lower risk of nephropathy in American Indians.